Screening of Indigenous Yeast From Different Ecological Region of Kathmandu Valley and Its Application in Wine Production - Rajopadhyaya, Bipanab; Maharjan, Bipana; Maharjan, Roshani; Acharya, Amrit (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The aim of the study was to isolate and screen the potent yeast from the air for implementing new yeast in wine fermentation. Methods: In this study, 35 air samples collected in sterile grape juice in glass jar and left over for four days exposure for the growth of yeast from different locations around the Kathmandu Valley. Yeasts were screened by culturing on selective Ethanol Sulfite Agar (ESA) media at 30°C for 2-3 days in Microbiology Lab of Pinnacle College. Yeast isolates were characterized based on colony morphology, microscopic characteristics, Fermentative capacity, Hydrogen sulfide production. Selected yeast isolates were subjected to ethanol fermentation and tested for alcohol tolerance capacity. Wine quality was assessed by sensory evaluation. Results: Of 35 samples, only 20 yeast isolates were isolated. Among these isolates, the variation in colony characteristics along with oval and ellipsoidal microscopic appearance was observed. All the isolates were able to ferment major sugars such as glucose, fructose and sucrose, but few could not ferment galactose and maltose, while none-fermented lactose and xylose. Here, isolates showing no H2S (L29, L34) and mild H2S producer (isolate L31) were subjected to ethanol fermentation. Also, Comparative analysis was made by using commercial standard wine yeast (STAN). Rapid fermentation of grape juice with initial 21 0Brix was observed in L31 isolate, which produced 12.99% v/v alcohol with titratable acidity (TA) 5.25 g/L, followed by L29 strain with 11.99%v/v alcohol and 4.5 g/L TA which were higher than STAN (10.99% alcohol). These isolates specified as Ethanol tolerance up to 13%v/v, while none of them were able to grow at 15% v/v ethanol concentration and 45°C temperature. However, significant growth was observed at pH 3 along with sugar tolerance capacity at 30 0Brix. The wine produced by these isolates was found to be remarkably different among each other. While the sensory analysis of wine led to isolate L31 being congenial to tasters. Conclusion: L31 isolate was found to be efficient and advantageous for wine production indicating its industrial application.